Vertebrate Nup53 Interacts with the Nuclear Lamina and Is Required for the Assembly of a Nup93-containing Complex - Hawryluk-Gara, Lisa A. (The American Society for Cell Biology, 2005)
The nuclear pore complex (NPC) is an evolutionarily conserved structure that mediates exchange of macromolecules across the nuclear envelope (NE). It is comprised of ∼30 proteins termed nucleoporins that are each present in multiple copies. We have investigated the function of the human nucleoporin Nup53, the ortholog of Saccharomyces cerevisiae Nup53p. Both cell fractionation and in vitro binding data suggest that Nup53 is tightly associated with the NE membrane and the lamina where it interacts with lamin B. We have also shown that Nup53 is capable of physically interacting with a group of nucleoporins including Nup93, Nup155, and Nup205. Consistent with this observation, depletion of Nup53 using small interfering RNAs causes a decrease in the cellular levels of these nucleoporins as well as the spindle checkpoint protein Mad1, likely due to destabilization of Nup53-containing complexes. The cellular depletion of this group of nucleoporins, induced by depleting either Nup53 or Nup93, severely alters nuclear morphology producing phenotypes similar to that previously observed in cells depleted of lamin A and Mad1. On basis of these data, we propose a model in which Nup53 is positioned near the pore membrane and the lamina where it anchors an NPC subcomplex containing Nup93, Nup155, and Nup205.